Acceptance and feasibility of novel staple foods among individuals with type 2 diabetes in Singapore: a mixed methods study - Hafizah Yusri; Sean Jun Leong Ou; Dimeng Yang; Marcus Ting; Wei Lin Liew; Salome A. Rebello; Chin Meng Khoo; E. Shyong Tai; E. Shyong Tai; Mei Hui Liu (Frontiers in Nutrition)
IntroductionNovel staple foods (NVSFs) are defined as modified staple foods that provide healthier alternatives to type 2 diabetes (T2D) patients aiming to improve postprandial glycemic responses. We explored the expectations and perceptions of participants with T2D toward NVSFs alongside their feasibility using a mixed methods approach.MethodsThree distinct NVSFs were investigated: (i) bread fortified with anthocyanins for carbohydrase inhibition; (ii) white rice fortified with fiber; and (iii) microfluidic gel noodles reduced in available carbohydrates. Sixteen individuals with T2D participated in a 5-week crossover study where NVSFs or control staple foods were consumed in mixed meals for breakfast, lunch, and dinner. Participants wore continuous glucose monitoring devices during interventions to measure postprandial glycemic responses and interviews were conducted before and after interventions.ResultsQualitative analysis from interviews identified participants’ prior dietary choices, prior NVSF perceptions, expectations, and impressions, trade-offs between sensory and healthfulness, price, modification methods, and other socio-economic regular consumption considerations as key factors contributing to the acceptance of NVSFs. Among the NVSFs, the anthocyanin-fortified bread and fiber-fortified rice were preferred for their palatability, but not the microfluidic noodles. However, quantitative analysis from continuous glucose monitoring revealed only the microfluidic noodle meal demonstrating a significant reduction in 2-h iAUC value relative to its control from 160.2 ± 17.6 to 114.3 ± 12.2 mmol/L.min (mean ± SEM) p = 0.046.DiscussionThis highlights the challenge of attaining a balance between health and favorable sensory properties for these NVSFs, which may be attributed to their modification methods. We conclude that an alternative staple food with palatable taste and texture properties modified through the reduction of available carbohydrates may be an effective approach to enhance the acceptance and feasibility of modified staple foods for T2D management.